Peroral endoscopic myotomy (POEM) vs laparoscopic Heller myotomy (LHM) for the treatment of Type III achalasia in 75 patients: a multicenter comparative study - Kumbhari, Vivek; Tieu, Alan H; Onimaru, Manabu; El Zein, Mohammad H.; Teitelbaum, Ezra N.; Ujiki, Michael B.; Gitelis, Matthew E.; Modayil, Rani J.; Hungness, Eric S.; Stavropoulos, Stavros N.; Shiwaku, Hiro; Kunda, Rastislav; Chiu, Philip; Saxena, Payal; Messallam, Ahmed A.; Inoue, Haruhiro; Khashab, Mouen A. (Endoscopy International Open, 2015)
Background and study aims: Type III achalasia is characterized by rapidly propagating pressurization attributable to spastic contractions. Although laparoscopic Heller myotomy (LHM) is the current gold standard management for type III achalasia, peroral endoscopic myotomy (POEM) is conceivably superior because it allows for a longer myotomy. Our aims were to compare the efficacy and safety of POEM with LHM for type III achalasia patients.Patients and methods: A retrospective study of 49 patients who underwent POEM for type III achalasia across eight centers were compared to 26 patients who underwent LHM at a single institution. Procedural data were abstracted and pre- and post-procedural symptoms were recorded. Clinical response was defined by improvement of symptoms and decrease in Eckardt stage to ≤ 1. Secondary outcomes included length of myotomy, procedure duration, length of hospital stay, and rate of adverse events.Results: Clinical response was significantly more frequent in the POEM cohort (98.0 % vs 80.8 %; P = 0.01). POEM patients had significantly shorter mean procedure time than LHM patients (102 min vs 264 min; P < 0.01) despite longer length of myotomy (16 cm vs 8 cm; P < 0.01). There was no significant difference between POEM and LHM in the length of hospital stay (3.3 days vs 3.2 days; P = 0.68), respectively. Rate of adverse events was significantly less in the POEM group (6 % vs 27 %; P < 0.01).Conclusions: POEM allows for a longer myotomy than LHM, which may result in improved clinical outcomes. POEM appears to be an effective and safe alternative to LHM in patients with type III achalasia.